Lasertherapy for the control of gustative and/or olfactory disorders resulting from infection by the SARS-CoV-2 virus: Pilot study (Research, Society and Development, 2024)
Introduction: Olfactory and gustatory dysfunctions resulting from the inflammatory process caused by SARS-CoV-2 have been frequently reported by patients. In view of this, photobiomodulation, a non-invasive method capable of providing biostimulatory, anti-inflammatory and regenerative effects, has been presented as a coherent approach to be used in the control of COVID-19 symptoms. Aim: To evaluate the effectiveness of the application of different therapeutic protocols of photobiomodulation in olfactory and gustatory dysfunctions resulting from infection by the SARS-CoV-2 virus. Methodology: Pilot Study of a Randomized Clinical Trial. Sample consisting of people who had COVID-19 and who still complained of partial and/or total olfactory and/or gustatory dysfunction three months after infection with SARS-CoV-2. Clinical and demographic data were collected from the clinical examination form, different photobiomodulation protocols were applied and the participants were evaluated for improvement or worsening of alterations with the performance of gustatory and olfactory tests. All information collected in the study was typed and conducted using the IBM SPSS Statistics computer program, version 29.0. Results: Participants showed improvement in olfactory and gustatory sensory perceptions in relation to the first tests performed at the beginning of the study, in all subgroups, and moved on to the follow-up phase for a period of 3, 6, 9 and 12 months. Conclusion: Laser therapy is a promising therapeutic method in the treatment of gustatory and olfactory disorders resulting from SARS-CoV-2 infection.